The contribution of anxiety to high school students learning motivation in online learning - Komarudin (International Journal of Health Science and Technology, 2024)
The COVID-19 pandemic has brought a change from face-to-face learning to online learning; thus giving rise to students' anxiety. This study aims to determine the contribution of anxiety to the learning motivation of senior high school students in online learning. This research is designed in the form of quantitative research methods. The population consists of high school students in Yogyakarta with a research sample of 80 students. The sampling technique uses probability sampling. The data collection tool uses a learning motivation scale developed by researchers based on aspects of perseverance in learning, tenacious in facing difficulties, interest and sharpness of attention in learning, achievement in learning, and independence in learning. The learning motivation scale has an alpha Cronbach reliability coefficient of 0.940. Meanwhile, the scale of disability was developed by researchers based on aspects of heart, cognitive, somatic, and motor with an alpha Cronbach reliability coefficient of 0.860. Data analysis was carried out using the statistical analysis method of product-moment correlation from Pearson with the help of SPSS release 16. The results of the data analysis obtained a significant value of 0.002 (p < 0.05) and a correlation coefficient of -0.320, which means that there is a significant negative relationship between anxiety and student learning motivation in online learning. The coefficient of determination of 0.103 shows that anxiety contributes of 10.30% to the motivation of upper-secondary students in online learning, while 89.70% is influenced by other factors that were not involved in this study.